A fractional Hopf Lemma for sign-changing solutions - Dipierro, Serena; Soave, Nicola; Valdinoci, Enrico (Communications in partial differential equations, 2024)
In this paper we prove some results on the boundary behavior of solutions to fractional elliptic problems. Firstly, we establish a Hopf Lemma for solutions to some integro-differential equations. The main novelty of our result is that we do not assume any global condition on the sign of the solutions. Secondly, we show that non-trivial radial solutions cannot have infinitely many zeros accumulating at the boundary. We provide concrete examples to show that the results obtained are sharp.